(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Haematoma auris is a collection of serosanguinous fluid between perichondrium and cartilage of pinna. Various method of aspiration / incision and pressure bandage used to treat the condition, here we are using steroid at the site after aspiration with a needle, no pressure bandage or drain used. Total 49 patients were treated with no untoward events. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 83-87